Preparation method and application of lithium iron titanate / carbon quantum dot composite material
By using bronze phase titanium dioxide and carbon quantum dots to prepare Li2FeTiO4/carbon quantum dot composite materials, the problem of poor electrochemical performance of Li2FeTiO4 positive electrode material is solved, and efficient and stable lithium storage and long cycle life of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411897634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Li2FeTiO4 cathode material has problems of slow kinetics and poor electrochemical performance, which limits its application in electrochemical energy storage.
Li2FeTiO4/carbon quantum dot composite material is prepared by hydrothermal activation and pickling treatment, and the electrochemical performance of the material is improved by using the conductivity and chemical stability of the carbon quantum dots.
It significantly improves the charging and discharge rate and rate performance of lithium-ion batteries, improves the stability and cycle life of materials, reduces the interface impedance, and is suitable for large-scale commercial production.
Smart Images

Figure CN119674024A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a preparation method and application of a lithium iron titanate / carbon quantum dot composite material. Background Art
[0002] With the rapid development of society and the improvement of people's living standards, energy demand continues to grow. Traditional fossil fuels are not only limited in resources, but also produce a large amount of greenhouse gases and other pollutants during use, which has a serious impact on the environment. Therefore, the development of clean and renewable new energy materials has become the focus of current research. As a highly efficient energy storage device, lithium-ion batteries have been widely used in electric vehicles, portable electronic devices and other fields. However, with the continuous growth of energy demand and the rapid development of science and technology, higher requirements are placed on the energy density, cycle stability and safety of lithium-ion batteries. As an important component of lithium-ion batteries, the physical and chemical properties of positive electrode materials determine the capacity, charge and discharge speed and service life of the battery. Therefore, the research and development of high-performance positive electrode materials has become the key to the development of lithium-ion battery technology.
[0003] Li 2 FeTiO 4 The cathode material system has attracted great attention because it can coordinate the redox reaction of transition metal cations and anions to obtain high capacity, and has been tried by many researchers in the field of lithium-ion battery energy storage. 2 FeTiO 4 There is a lack of ion and electron transport channels, which leads to slow kinetics and poor electrochemical performance, so its application in electrochemical energy storage is greatly limited. 2 FeTiO 4 The Ti source of the positive electrode material is usually anatase and rutile TiO 2 , while the bronze phase TiO 2 As a metastable state, its research and application are still insufficient. It is worth exploring whether it can be used as a Ti source for lithium iron titanate cathode materials. 2 How to prepare Ti source as positive electrode material for lithium-ion batteries also requires in-depth research.
[0004] On the other hand, it is reported that the composite with nanomaterials can enhance the reaction kinetics, reduce the interface resistance, promote the rapid transmission of electrons and ions, and is expected to achieve efficient lithium storage. 2 FeTiO 4 There is a lack of systematic reports on the composite cathode material system. In particular, how to optimize the nanomaterials and Li 2 FeTiO4 The interface interaction can reduce the interface resistance, thereby regulating its Li 2 FeTiO 4 The electrochemical effects of the material are unknown.
[0005] At the same time, the type of nanocomposite material is of great significance to obtain materials with stable structure and excellent performance. 2 FeTiO 4 The particles form a tight bond, improving the overall conductivity of the composite material. However, graphene materials are highly hydrophilic and easily adsorb water molecules to produce chemical reactions, thus affecting the stability and electrochemical properties of the composite material. Carbon quantum dots (CDs), as a new type of zero-dimensional carbon material, have the characteristics of excellent conductivity, good chemical stability and high specific surface area, and are considered to be an ideal modifier.
[0006] Although carbon quantum dots have certain advantages as a conductive material in the field of electrochemistry, how to combine carbon quantum dots with Li 2 FeTiO 4 It is still technically challenging to effectively combine and give full play to their role. Although the application of carbon quantum dots in battery materials has been studied, how to ensure their uniform dispersion and stable composite with lithium iron titanate materials is still a technical difficulty. In particular, how to control the composite process through methods such as sol-gel method, ensure the interaction between lithium iron titanate and carbon quantum dots, and avoid agglomeration and instability caused by too many carbon quantum dots is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a preparation method and application of a lithium iron titanate / carbon quantum dot composite material. The present invention composites carbon quantum dots with lithium iron titanate to form a lithium ion battery positive electrode composite material with enhanced electrochemical performance. The preparation process is simple, the cost is low, and it is suitable for large-scale commercial production.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a lithium iron titanate / carbon quantum dot composite material, the preparation method comprising the following steps:
[0010] (1) Anatase and sodium hydroxide are used as raw materials, uniformly mixed in deionized water, and then subjected to ultrasonic treatment and hydrothermal activation to obtain an activated product, sodium titanate;
[0011] (2) Repeatedly centrifuging and adding deionized water to the activated product sodium titanate until the pH of the supernatant is ≤10, then adding dilute hydrochloric acid and stirring for 2-4 hours, repeating the operation until the supernatant is neutral, and drying to obtain an acid-washed product;
[0012] (3) The pickled product is ground, sieved, and calcined to obtain bronze phase TiO 2 (B);
[0013] (4) Using citric acid as chelating agent, CH 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2 (B) Li, Fe, Ti sources, and a certain mass fraction of carbon quantum dots dissolved in anhydrous ethanol;
[0014] (5) stirring the mixture obtained in step (4) in a water bath to obtain a gel, vacuum drying and sieving, and calcining in an inert atmosphere to obtain a pre-calcined material;
[0015] (6) The pre-sintered material is ball-milled and sieved in sequence, and finally sintered under an inert atmosphere to obtain Li 2 FeTiO 4 / Carbon quantum dot composite materials.
[0016] Preferably, the mass ratio of anatase to sodium hydroxide in step (1) is 1:34-37, and the ultrasonic treatment time is 20-40 min.
[0017] Preferably, the hydrothermal activation in step (1) is carried out in a sealed reactor, the activation temperature is 150-170°C, the heating rate is 7-8°C / s, and the hydrothermal activation time is 20-24h.
[0018] Furthermore, the anatase in step (1) is commercial anatase; 70-85 ml of deionized water is used for every 1 g of anatase.
[0019] Preferably, the concentration of the dilute hydrochloric acid in step (2) is 0.1-0.2 M; the drying temperature is 70-90° C., and the drying time is 10-12 h.
[0020] Furthermore, the neutrality of the supernatant in step (2) means that its pH is about 7.
[0021] Preferably, the screening in step (3) is through a 150-200 mesh standard sieve; the calcination atmosphere is air, the calcination temperature is 340-360°C, the time is 2-4h, and the heating rate is 4-6°C / min.
[0022] Preferably, the mass fraction of the carbon quantum dots in step (4) is 1-5% of the sum of the three sources of Li, Fe and Ti; and the molar ratio of the citric acid to the sum of the Fe ions and the Ti ions is 1-2:1.
[0023] Preferably, in step (4), CH 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2 The mass ratio of (B) is 2.56:2.49:1.
[0024] Furthermore, in step (4), 8-16 ml of anhydrous ethanol is used per 1 g of citric acid.
[0025] Preferably, the water bath temperature in step (5) is 60-70°C, and the stirring time is 4-6h; the drying temperature is 100-120°C, and the time is 10-12h; and the sieving is through a 60-100 mesh standard sieve.
[0026] Preferably, the calcination atmosphere in step (5) is argon, the calcination temperature is 400-600°C, the time is 7-10h, and the heating rate is 4-6°C / min.
[0027] Preferably, the screening in step (6) is through a 100-300 mesh standard sieve; the calcination atmosphere is argon, the calcination temperature is 600-700°C, the time is 7-9h, and the heating rate is 4-6°C / min.
[0028] Furthermore, the ball milling process described in step (6) uses anhydrous ethanol as the medium and the ball milling time is 2-4 hours.
[0029] The reaction principles of the above steps and the factors affecting the process parameter settings are as follows:
[0030] The activation step of step (1) effectively breaks and reorganizes the ionic bonds of titanium oxide and covalent bonds in anatase and the ionic bonds of sodium hydroxide, thereby obtaining sodium titanate. Too high an activation temperature may lead to overreaction or decomposition of the raw materials, while too low a temperature may not achieve the expected activation effect; the same is true for the holding time during activation. If the time is too short, the raw materials will not react fully and the expected activation effect will not be achieved. If the time is too long, the raw materials will overreact or unnecessary energy consumption will occur.
[0031] The purpose of pickling in step (2) is to remove residual Na + , effectively remove impurities and improve TiO 2 (B) Purity.
[0032] The calcination in step (3) can make the chemical bonds in the raw materials more easily broken and recombined, which is beneficial to the formation of bronze phase titanium dioxide, i.e., TiO 2 (B) Formation of crystal phase. The preparation conditions of bronze phase titanium dioxide are different from those of other phases of titanium dioxide. For example, for the preparation of anatase titanium dioxide, polyvinyl alcohol is usually used as a dispersant, and a hydrothermal reaction is carried out at a high temperature (200°C). After acid washing and high-temperature calcination, anatase titanium dioxide is finally obtained. This is because anatase titanium dioxide is usually more stable at higher temperatures, so the reaction conditions are more intense and the reaction temperature is higher, which is conducive to the formation of anatase titanium dioxide.
[0033] The present invention adopts commercial anatase TiO 2 The bronze phase titanium dioxide is obtained by hydrothermal activation with sodium hydroxide at a relatively low temperature (about 160°C), acid washing and low temperature calcination (about 350°C). 2 It already has a relatively stable crystal structure. After hydrothermal reaction and acid exchange, the structure of sodium titanate is converted into titanate nanotubes. The calcination process can more effectively maintain the bronze phase titanium dioxide (TiO 2 (B)) crystal form.
[0034] Anatase TiO 2 It is easy to transform into rutile or other crystal forms at higher temperatures, but under certain conditions (such as appropriate hydrothermal activation conditions and acid exchange treatment), it is more inclined to form bronze phase TiO 2 (B). Too high a calcination temperature can lead to phase transformation or grain growth, increasing the formation of by-products; a suitable calcination time helps ensure the full removal of impurities while avoiding degradation of product performance due to over-calcination.
[0035] If the water bath temperature in step (5) is too high or the stirring time is too short, the reactants may not be fully dissolved and mixed, and the gel may not be formed uniformly, which may affect the structure and performance of the composite material during the subsequent calcination process. On the contrary, if the water bath temperature is too low or the stirring time is too long, the energy consumption and time cost will be increased, which is not conducive to industrial production.
[0036] If the calcination temperature in step (6) is too high, Li 2 FeTiO 4 Excessive grain growth reduces the specific surface area and ion diffusion rate of the composite material. At the same time, too high a temperature may cause the carbon quantum dots to agglomerate or sinter, reducing their dispersibility and stability in the composite material. On the contrary, if the calcination temperature is too low or the time is insufficient, the reactants cannot fully react, and there will be unreacted residues or impurities, affecting their purity and performance.
[0037] The present invention also provides an application of the lithium iron titanate / carbon quantum dot composite material obtained by the preparation method. The lithium iron titanate / carbon quantum dot composite material is used as a positive electrode material for lithium ion batteries to achieve efficient and stable lithium storage.
[0038] The beneficial technical effects of the present invention are:
[0039] 1. The present invention prepares Li by preparing bronze phase titanium dioxide as a Ti source 2 FeTiO 4 / CDs composites, TiO 2 (B) It has a unique crystal structure and electronic properties, which can effectively promote the embedding and de-embedding process of lithium ions, further optimize the transmission path of lithium ions, reduce diffusion resistance, and thus significantly improve the charge and discharge rate and rate performance of lithium-ion batteries.
[0040] 2. The present invention adopts a sol-gel method to 2 FeTiO 4 / Carbon quantum dot composite materials are used in the research and preparation of lithium-ion batteries. By adjusting the mass fraction of carbon quantum dots in the precursor, the amount and distribution of carbon quantum dots can be precisely controlled. The stability and high efficiency of the composite material obtained by the present invention have been verified and optimized through multiple rounds of experiments. 2 FeTiO 4 The surface of the particles forms a denser coating layer, thereby effectively improving the conductivity and lithium ion diffusion rate of the composite material.
[0041] 3. Carbon quantum dot nanomaterials as conductive bridges can not only improve the conductivity of materials, but also reduce the electron transfer resistance inside the material and optimize the charge distribution in the composite material through their unique structure and electronic properties, reducing charge accumulation. On the one hand, they can improve the conductivity and structural stability of the positive electrode material, and on the other hand, they can effectively increase the charge transfer rate, reduce the interface impedance, improve the rate performance of the battery, and extend the cycle life of lithium-ion batteries. The experimental results show that lithium iron titanate composite materials with appropriate amounts of carbon quantum dots show significant performance improvements at different rates, especially at high rate discharge, the composite material shows a more stable capacity retention rate and excellent cycle performance.
[0042] 4. The present invention cleverly combines bronze phase titanium dioxide and carbon quantum dots with iron-based disordered rock salt lithium iron titanate positive electrode materials to improve the safety performance of lithium-ion batteries. The preparation cost of carbon quantum dots is relatively low, which is conducive to reducing the overall cost of composite materials. The present invention has a high reproducibility and a simple preparation process, and is suitable for large-scale commercial production. Therefore, the preparation method of the lithium iron titanate / carbon quantum dot composite material provided by the present invention provides a new idea and method for the development of high-performance lithium-ion battery positive electrode materials, which has important scientific significance and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Preparation of Li for Examples 1-6 2 FeTiO 4 Flow chart of / CDs composite materials;
[0044] Figure 2 The TiO prepared in Example 1 2 (B) SEM image;
[0045] Figure 3 Li prepared in Example 4 2 FeTiO 4 SEM images of / CDs composites;
[0046] Figure 4 Li prepared in Example 4 2 FeTiO 4 / CDs composite material charge and discharge curves for the first three cycles;
[0047] Figure 5 Li prepared in Example 1-5 2 FeTiO 4 / CDs composite material rate performance test;
[0048] Figure 6 Li prepared in Example 1-5 2 FeTiO 4 / CDs composite material cycle performance test;
[0049] Figure 7 Li prepared in Example 4 and Comparative Example 1 2 FeTiO 4 Materials and Li 2 FeTiO 4 / CDs composite material cyclic performance test. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] If there is no special description of raw materials or processing techniques, it means that they are all conventional commercially available raw materials or conventional processing techniques in the field.
[0052] The carbon quantum dots CDs used in the following examples were prepared by a citric acid hydrothermal method. The specific steps are as follows: 0.2 g of citric acid and 20 mL of a 0.1 mol / L NaOH solution were co-transferred into a Teflon-lined stainless steel autoclave (50 mL), heated to 200 ° C, heated for 3 h, and a heating rate of 5 ° C / min. After the reaction was completed, the stainless steel autoclave was allowed to cool naturally, and the aqueous solution was centrifuged to obtain a carbon dot solution. Finally, the residual NaOH was separated with a dialysis membrane, and the treated solution was freeze-dried to obtain carbon dot powder CDs with an average particle size of 3 nm.
[0053] Embodiment 1-5:
[0054] (1) The preparation process of Examples 1-5 is as follows Figure 1 As shown in the figure, 0.315 g of commercial anatase and 11.2 g of sodium hydroxide were used as raw materials to prepare TiO 2 (B), uniformly mixed in 24.5 ml of deionized water, then subjected to ultrasonic treatment for 30 min, transferred into a reaction kettle, sealed, heated to 160°C at a heating rate of 7.7 s / °C and kept warm for 24 h for hydrothermal activation treatment.
[0055] (2) The activated product sodium titanate was subjected to a “centrifugation-adding deionized water-measuring pH” treatment until the pH of the supernatant was ≤10, 0.1 M dilute hydrochloric acid was added and stirred, and the “centrifugation-adding deionized water-measuring pH” was repeated until the pH of the supernatant was 7, and dried at 80° C. for 12 h to obtain an acid-washed product;
[0056] (3) The acid-washed product was ground and passed through a 200-mesh standard sieve. The sieved sample was calcined in an air atmosphere at a temperature of 350°C for 3 hours at a heating rate of 5°C / min to obtain TiO 2 (B);
[0057] (4) Using citric acid as chelating agent, CH 3 COOLi·2H 2 O is the Li source, FeCl 2 ·4H 2 O is the Fe source, TiO 2 (B) is the Ti source, which is weighed according to the molar ratio of n (citric acid): n (transition metal ions Fe and Ti) = 1.25:1. With ethanol as the medium, 12 ml of anhydrous ethanol is added to every 1 gram of citric acid. 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2The mass ratio of (B) is 2.56:2.49:1 for weighing, and 1%, 2%, 3%, 4% and 5% of the sum of the mass of Li, Fe and Ti sources are added to Examples 1-5 respectively, and the mixture is thoroughly mixed.
[0058] (5) stirring in a water bath at 65° C. for 5 h to obtain a wet gel, and vacuum drying at 120° C. for 12 h and passing through an 80-mesh standard sieve to obtain a dry gel; calcining the dry gel at a high temperature in an argon atmosphere, wherein the calcination temperature is 500° C., the calcination time is 8 h, and the heating rate is 5° C. / min to obtain a pre-calcined material.
[0059] (6) The pre-calcined sample was ball-milled for 3 h and passed through a 200-mesh standard sieve, and then calcined at a high temperature in an argon atmosphere at a temperature of 650° C. for 8 h at a heating rate of 5° C. / min to obtain a sample.
[0060] (7) Li 2 FeTiO 4 / CDs composite positive electrode material (80wt%), acetylene black (10wt%) and polyvinylidene fluoride (PVDF, 10wt%) are combined to form a positive electrode slurry. After the slurry is evenly spread on aluminum foil, it is dried at 80°C overnight. Cut into 10mm pole pieces, the loading amount is controlled at 1.0-1.3mg, argon is used as the filling gas, Celgard2400 is used as a diaphragm in a glove box, Li is used as a counter electrode, KLD-LFP01 is used as an electrolyte, and a CR2032 battery shell is used to assemble a half-cell and measure its electrochemical performance.
[0061] TiO prepared in Example 1 2 (B) SEM Figure 2 As shown in the figure, it can be seen that the prepared material is a relatively regular sheet or rod-like structure with a relatively smooth surface and high crystallinity. The SEM morphology shows obvious crystal planes and hierarchical structures, showing that the bronze phase TiO 2 Typical characteristics.
[0062] Example 4 Li prepared 2 FeTiO 4 SEM images of / CDs composites Figure 3 As shown in the figure, it can be seen that the sample prepared in Example 4 presents a larger and regular particle size and more evenly distributed carbon quantum dots. This shows that the addition of CDs not only improves the ion diffusion rate and storage capacity, but also effectively improves the charge and discharge performance. At the same time, CDs helps to maintain the stable structure of the material and slow down the capacity decay.
[0063] Embodiment 6:
[0064] (1) In this example, 0.315 g of commercial anatase and 10.71 g of sodium hydroxide were used as raw materials to prepare TiO 2 (B), uniformly mixed in 22.05 ml of deionized water, then subjected to ultrasonic treatment for 20 min, transferred into a reaction kettle, sealed, heated to 150°C at a heating rate of 7 s / °C and kept at this temperature for 20 h for hydrothermal activation treatment.
[0065] (2) The activated product sodium titanate was subjected to a "centrifugation-adding deionized water-measuring pH" treatment until the pH of the supernatant was ≤10, 0.1 M dilute hydrochloric acid was added and stirred, and the "centrifugation-adding deionized water-measuring pH" was repeated until the pH of the supernatant was 7, and dried at 70°C for 10 h to obtain an acid-washed product.
[0066] (3) The acid-washed product was ground and passed through a 150-mesh standard sieve. The sieved sample was calcined in an air atmosphere at a temperature of 340°C for 2 h at a heating rate of 4°C / min to obtain TiO 2 (B);
[0067] (4) Using citric acid as chelating agent, CH 3 COOLi·2H 2 O is the Li source, FeCl 2 ·4H 2 O is the Fe source, TiO 2 (B) is the Ti source, which is weighed according to the molar ratio of n (citric acid): n (transition metal ions Fe and Ti) = 1.25:1. Ethanol is used as the medium. 8 ml of anhydrous ethanol is required for every 1 gram of citric acid. 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2 The mass ratio of (B) is 2.56:2.49:1, and carbon quantum dots of 2% of the total mass of Li, Fe and Ti sources are added and mixed thoroughly.
[0068] (5) Stirring in a water bath at 60° C. for 4 h to obtain a wet gel, vacuum drying at 100° C. for 10 h and passing through a 60-mesh standard sieve to obtain a dry gel; calcining the dry gel at high temperature in an argon atmosphere, wherein the calcination temperature is 400° C., the time is 7 h, and the heating rate is 4° C. / min to obtain a pre-calcined material.
[0069] (6) The pre-calcined sample was ball-milled for 2 h and passed through a 100-mesh standard sieve, and then calcined at a high temperature in an argon atmosphere at a temperature of 600° C. for 7 h at a heating rate of 4° C. / min to obtain a sample.
[0070] (7) Li 2 FeTiO4 / CDs composite positive electrode material is assembled into a half-cell, and the specific method is the same as Example 1.
[0071] Embodiment 7:
[0072] (1) In this example, 0.315 g of commercial anatase and 11.67 g of sodium hydroxide were used as raw materials to prepare TiO 2 (B), uniformly mixed in 26.78 ml of deionized water, then subjected to ultrasonic treatment for 40 min, transferred into a reaction kettle, sealed, heated to 170°C at a heating rate of 8°C / s and kept warm for 24 h for hydrothermal activation treatment.
[0073] (2) The activated product sodium titanate was subjected to a "centrifugation-adding deionized water-measuring pH" treatment until the pH of the supernatant was ≤10, 0.2 M dilute hydrochloric acid was added and stirred, and the "centrifugation-adding deionized water-measuring pH" was repeated until the pH of the supernatant was 7, and dried at 90° C. for 12 h to obtain an acid-washed product;
[0074] (3) The acid-washed product was ground and passed through a 200-mesh standard sieve. The sieved sample was calcined in an air atmosphere at a temperature of 360°C for 4 hours at a heating rate of 6°C / min to obtain TiO 2 (B);
[0075] (4) Using citric acid as chelating agent, CH 3 COOLi·2H 2 O is the Li source, FeCl 2 ·4H 2 O is the Fe source, TiO 2 (B) is the Ti source, which is weighed according to the molar ratio of n (citric acid): n (transition metal ions Fe and Ti) = 1.25:1. Ethanol is used as the medium. 16 ml of anhydrous ethanol is required for every 1 gram of citric acid. 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2 The mass ratio of (B) is 2.56:2.49:1, and carbon quantum dots of 3% of the total mass of Li, Fe and Ti sources are added and mixed thoroughly.
[0076] (5) stirring in a water bath at 70° C. for 6 h to obtain a wet gel, and vacuum drying at 120° C. for 12 h and passing through a 100-mesh standard sieve to obtain a dry gel; calcining the dry gel at a high temperature in an argon atmosphere, wherein the calcination temperature is 600° C., the time is 10 h, and the heating rate is 6° C. / min to obtain a pre-calcined material.
[0077] (6) The pre-calcined sample was ball-milled for 4 h and passed through a 300-mesh standard sieve, and then calcined at a high temperature in an argon atmosphere at a temperature of 700° C. for 9 h at a heating rate of 6° C. / min to obtain a sample.
[0078] (7) Li 2 FeTiO 4 / CDs composite positive electrode material is assembled into a half-cell, and the specific method is the same as Example 1.
[0079] Comparative Example 1:
[0080] (1) In this comparative example, 0.315 g of commercial anatase and 11.2 g of sodium hydroxide were used as raw materials to prepare TiO 2 (B), uniformly mixed in 24.5 ml of deionized water, then subjected to ultrasonic treatment for 30 min, transferred into a reaction kettle, sealed, heated to 160°C at a heating rate of 7.7 s / °C and kept warm for 24 h for hydrothermal activation treatment.
[0081] (2) The activated product sodium titanate was subjected to a “centrifugation-adding deionized water-measuring pH” treatment until the pH of the supernatant was ≤10, 0.1 M dilute hydrochloric acid was added and stirred, and the “centrifugation-adding deionized water-measuring pH” was repeated until the pH of the supernatant was 7, and dried at 80° C. for 12 h to obtain an acid-washed product;
[0082] (3) The acid-washed product was ground and passed through a 200-mesh standard sieve. The sieved sample was calcined in an air atmosphere at a temperature of 350°C for 3 hours at a heating rate of 5°C / min to obtain TiO 2 (B);
[0083] (4) Using citric acid as chelating agent, CH 3 COOLi·2H 2 O is the Li source, FeCl 2 ·4H 2 O is the Fe source, TiO 2 (B) is the Ti source, which is weighed according to the molar ratio of n (citric acid): n (transition metal ions Fe and Ti) = 1.25:1. Ethanol is used as the medium. 12 ml of anhydrous ethanol is required for every 1 gram of citric acid. 3 COOLi·2H 2 O, FeCl 2 ·4H 2 O、TiO 2 The mass ratio of (B) was 2.56:2.49:1, and 0% carbon quantum dots were added and mixed thoroughly.
[0084] (5) stirring in a water bath at 65° C. for 5 h to obtain a wet gel, and vacuum drying at 120° C. for 12 h and passing through an 80-mesh standard sieve to obtain a dry gel; calcining the dry gel at a high temperature in an argon atmosphere, wherein the calcination temperature is 500° C., the calcination time is 8 h, and the heating rate is 5° C. / min to obtain a pre-calcined material.
[0085] (6) The pre-calcined sample was ball-milled for 3 h and passed through a 200-mesh standard sieve, and then calcined at a high temperature in an argon atmosphere, wherein the calcination temperature was 650° C., the time was 5 h, and the heating rate was 5° C. / min to obtain a sample.
[0086] (7) Li 2 FeTiO 4 / CDs composite positive electrode material is assembled into a half-cell, and the specific method is the same as Example 1.
[0087] Test example:
[0088] 1. Li 2 FeTiO 4 Electrochemical performance test of / CDs composite materials:
[0089] The electrochemical properties of the samples were determined by assembling a half-cell using a CHI660E electrochemical workstation and a lithium electrode as the counter electrode.
[0090] Example 4 Li prepared 2 FeTiO 4 The first three charge-discharge curves of the / CDs composite cathode material are as follows Figure 4 As shown in the figure, the battery's cyclic charge and discharge voltage range is 1.5-4.8 V. During the first charge, the voltage quickly rises from about 2.6 V to about 4.0 V, then rises slowly to 4.5 V, and a clear platform appears, which is consistent with the Li 2 FeTiO 4 / CDs composite materials. During the first discharge, the voltage dropped rapidly from 4.8V to about 3.4V, and then the voltage gradually dropped to about 1.7V and a platform appeared, indicating that the battery underwent a typical intercalation / deintercalation reaction during the charge and discharge process. The first charge and discharge specific capacities were 202.6mAh / g (charging) and 147.48mAh / g (discharging), respectively, showing good energy storage capacity. The charge and discharge curves of the second and third cycles overlapped highly, indicating that the battery had good electrochemical stability and small capacity attenuation in subsequent cycles, demonstrating the excellent cycle stability of the material in long-term use.
[0091] Li prepared in Example 1-5 2 FeTiO 4 The rate performance test of / CDs composite materials is as follows Figure 5As shown. The results show that the rate performance of Example 4 is significantly better than that of samples with other composite ratios. After 30 cycles, the capacity of Example 4 recovered to 119.4 mAh / g, and the capacity retention rate reached 84.6%, showing strong stability and high conductivity. Therefore, the compounding of an appropriate amount of carbon quantum dots significantly improves the conductivity and rate performance of the material, can effectively improve the conductivity of electrons and ions, enhance structural stability, and reduce capacity attenuation during high-rate discharge. However, too high or too low a composite ratio will cause the material to form an unstable structure and agglomeration, significantly reducing its electrochemical properties.
[0092] Li prepared in Example 1-5 2 FeTiO 4 Cyclic performance test of / CDs composites Figure 6 As shown, the initial discharge capacity of the sample in Example 1 is 125.14 mAh / g, the initial discharge capacity of the sample in Example 2 is 118.61 mAh / g, the initial discharge capacity of the sample in Example 3 is 110.83 mAh / g, the initial discharge capacity of the sample in Example 4 is 140.16 mAh / g, and the initial discharge capacity of the sample in Example 5 is 132.28 mAh / g. The electrochemical performance of Example 4 is significantly better than that of other examples, showing better cycle stability and lower capacity decay.
[0093] The initial discharge specific capacities of Example 6 and Example 7 are 107.51 mAh / g and 101.78 mAh / g, respectively, which are slightly lower than Example 2 (118.61 mAh / g) and Example 3 (110.83 mAh / g). According to the results, due to the differences in factors such as raw material ratio, reaction conditions and calcination temperature during the preparation process of Example 6 and Example 7, the crystal structure, surface properties, particle size distribution and other aspects of the materials are different. These structural changes directly affect the electrical conductivity, ion diffusion rate and electrochemical stability of the materials, thereby resulting in a decrease in battery performance. Therefore, the optimization of preparation conditions is crucial in improving the performance of lithium-ion batteries, especially in controlling the appropriate material microstructure and chemical composition while ensuring a high initial discharge specific capacity and a low capacity decay, so as to promote efficient charge transmission and reaction. In addition, the electrochemical performance results of Example 6 and Example 7 also provide an important experimental basis for further adjusting the synthesis process parameters and improving the material structure.
[0094] Li prepared in Example 4 and Comparative Example 1 2 FeTiO 4 Cyclic performance test of / CDs composites Figure 7As shown, the first cycle discharge specific capacities of Example 4 and Comparative Example 1 are 140.16 mAh / g and 92.2 mAh / g, respectively. The discharge specific capacities after 30 cycles are 118.59 mAh / g and 47.2 mAh / g, respectively, and the capacity retention rates are 84.61% and 51.19%, respectively. Compared with the sample of Comparative Example 1, the cycle performance of the sample of Example 4 is improved by about 33%. This shows that the addition of CDs effectively enhances the Li 2 FeTiO 4 The conductivity between molecules and between molecules and electrolytes improves the charge and discharge performance of the battery and the structural stability of the material. Carbon quantum dots have excellent conductivity and high specific surface area, which can reduce the resistance of the battery during the charge and discharge process and promote the rapid diffusion of lithium ions. At the same time, carbon quantum dots can improve the structural stability of the material, reduce volume expansion during repeated charge and discharge, and further improve the long-term stability of the material.
[0095] The present invention prepares bronze phase titanium dioxide as a Ti source, whose unique crystal structure and excellent electronic properties effectively promote the embedding and de-embedding process of lithium ions, thereby optimizing the transmission path of lithium ions. At the same time, the composite carbon quantum dot nanomaterial acts as a conductive bridge, which reduces the electron transmission resistance inside the material and improves the charge distribution in the composite material, reducing charge accumulation. These improvements enhance the Li 2 FeTiO 4 The conductivity and structural stability of the material can significantly extend the cycle life of lithium-ion batteries.
[0096] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a lithium iron titanate / carbon quantum dot composite material, characterized in that: The preparation method comprises the following steps: (1) Anatase and sodium hydroxide are used as raw materials, uniformly mixed in deionized water, and then subjected to ultrasonic treatment and hydrothermal activation to obtain an activated product, sodium titanate; (2) Repeatedly centrifuging and adding deionized water to the activated product sodium titanate until the pH of the supernatant is ≤10, then adding dilute hydrochloric acid and stirring for 2-4 hours, repeating the operation until the supernatant is neutral, and drying to obtain an acid-washed product; (3) grinding, sieving and calcining the pickled product to obtain bronze phase TiO2 (B); (4) Citric acid was used as a chelating agent, CH3COOLi·2H2O, FeCl2·4H2O, and TiO2(B) were used as Li, Fe, and Ti sources, respectively, and a certain mass fraction of carbon quantum dots were dissolved in anhydrous ethanol; (5) stirring the mixture obtained in step (4) in a water bath to obtain a gel, vacuum drying and sieving, and calcining in an inert atmosphere to obtain a pre-calcined material; (6) The pre-sintered material is ball-milled and sieved in sequence, and finally sintered under an inert atmosphere to obtain a Li2FeTiO4 / carbon quantum dot composite material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of anatase to sodium hydroxide in step (1) is 1:34-37, and the ultrasonic treatment time is 20-40 min; The hydrothermal activation in step (1) is carried out in a sealed reactor, the activation temperature is 150-170°C, the heating rate is 7-8°C / s, and the hydrothermal activation time is 20-24h.
3. The preparation method according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid in step (2) is 0.1-0.2M; the drying temperature is 70-90°C, and the drying time is 10-12h.
4. The preparation method according to claim 1, characterized in that: The sieving in step (3) is through a 150-200 mesh standard sieve; the calcination atmosphere is air, the calcination temperature is 340-360°C, the time is 2-4h, and the heating rate is 4-6°C / min.
5. The preparation method according to claim 1, characterized in that: The mass fraction of the carbon quantum dots in step (4) is 1-5% of the sum of the three sources of Li, Fe and Ti; the molar ratio of the citric acid to the sum of the Fe ions and the Ti ions is 1-2:
1.
6. The preparation method according to claim 1, characterized in that: The mass ratio of CH3COOLi·2H2O, FeCl2·4H2O and TiO2 (B) in step (4) is 2.56:2.49:
1.
7. The preparation method according to claim 1, characterized in that: The water bath temperature in step (5) is 60-70° C., and the stirring time is 4-6 h; the drying temperature is 100-120° C., and the time is 10-12 h; and the sieving is through a 60-100 mesh standard sieve.
8. The preparation method according to claim 1, characterized in that: The calcination atmosphere in step (5) is argon, the calcination temperature is 400-600°C, the time is 7-10h, and the heating rate is 4-6°C / min.
9. The preparation method according to claim 1, characterized in that: The screening in step (6) is through a 100-300 mesh standard sieve; the calcination atmosphere is argon, the calcination temperature is 600-700°C, the time is 7-9h, and the heating rate is 4-6°C / min.
10. Application of the lithium iron titanate / carbon quantum dot composite material obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The lithium iron titanate / carbon quantum dot composite material is used as a positive electrode material for lithium-ion batteries to achieve efficient and stable lithium storage.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate with excellent conductivity
CN115304044A
Lithium titanate / carbon quantum dot composite material, preparation method thereof and battery
CN115911307A
Positive-electrode active material for lithium-ion secondary battery and lithium-ion secondary battery
US20130017449A1
Lithium ion battery fast charging negative electrode material and preparation and use thereof
WO2024114079A1